Participation in Global Value Chains in Latin America Implications for Trade and Trade-Related Policy - Cadestin, Charles (OECD Trade Policy Papers, 2016)
This paper characterises the extent of GVC participation in selected countries of Latin America. It looks deeper into certain key trade policy-related aspects of Latin American trade integration with the potential to improve GVC participation. Latin America has a dense web of intra and extra-regional preferential trade agreements (PTAs). Nevertheless, the overlap, duplication and conflicts among the different rules and standards governing trade under these PTAs are likely reducing the benefits of these agreements. This is prompting renewed interest in the idea of linking or harmonising the various Latin American PTAs. To help inform this debate, this study analyses the impact of rules of origin (RoO) and non-tariff measures (NTMs) on GVC integration in the region, and examines relevant harmonisation initiatives